MOLECULAR AND CELLULAR BASES OF THE IMMUNE REGULATION, IMMUNODIAGNOSTICS AND IMMUNOTHERAPHY (EXPEREMENTAL MODELS) - Editorial article (Медицинская иммунология, 2014)
Молекулярные и клеточные основы иммунорегуляции, иммунодиагностики и иммунокоррекции (экспериментальные модели).